Throughput performance for full-duplex DF relaying protocol in hybrid wireless power transfer systems - Hoang-Phuong Van; Hoang-Sy Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Most of the existing studies on energy harvesting (EH) cooperative relaying networks are conducted for the outdoor environments which are mainly characterized by Rayleigh fading channels. However, there are not as many studies that consider the indoor environments whereas the state-of-the-art internet of things (IoT) and smart city applications are built upon. Thus, in this paper, we analyze a namely hybrid time-power splitting relaying (HTPSR) protocol in a full-duplex (FD) decode-and-forward (DF) battery-energized relaying network in indoor scenarios modelled by the unpopular log-normal fading channels. Firstly, we formulate the analytical expression of the outage probability (OP) then the system throughput. Accordingly, we simulate the derived expressions with the Monte Carlo method. It is worth mentioning that in our work, the simulation and the theory agree well with each other. From the simulation results, we know how to compromise either the power splitting (PS) or the time splitting (TS) factors for optimizing the system performance.